PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS ETNOMATEMATIKA PADA MATERI TRANSFORMASI - Ainiyah, Nila; Loviana, Selvi (Bahasa Indonesia, 2024)
This study aims to produce teaching materials in the form of ethnomathematics-based worksheets on Lampung batik motifs in understanding valid and practical geometric transformation concepts. The type of research used is Research and Development (R&D). This research produced a product in the form of ethnomathematics-based worksheets on transformation material at SMP PGRI Kesumadadi. The research procedure used is the Borg and Gall development model which goes through several stages including: potentials and problems, data collection, product design, design validation, design revision, product testing, and product revision. In the product trial stage, a limited trial was carried out involving 15 class IX students at SMP PGRI Kesumadadi. The research instruments used were material expert validation sheets, media expert validation sheets, and student response questionnaires. The results of this development research show that the assessment of the material expert validation obtained an average validation result of 88.12% with the validation criterion of "Very Valid". Furthermore, the results of the validation of media experts obtained an average validation result of 91.66% with the validation criterion of "Very Valid". The results of the analysis of the student response questionnaire at the limited trial stage obtained a percentage of 92.6% with the practicality criterion "Very Practical".